Adsorption-Deposition Behavior of Typical Minerals on Antimony in Soil - Guibin GUO; Xiaoya YUAN; Lijin HUANG; Qin SHUAI; Shenghong HU; Lei OUYANG (Yankuang ceshi)
Human activities such as mineral mining and coal combustion cause a large amount of antimony to enter into environmental soil. Exploring the adsorption deposition behavior of antimony on typical soil minerals is important for predicting the environmental fate of antimony and preventing its pollution. Thus, six kinds of commonly found metal hydroxides and clay minerals in soil (namely hematite, goethite, ferrihydrite, aluminum oxide, ramsdellite, and kaolinite) were selected to investigate the adsorption thermodynamic and kinetic behavior of Sb(Ⅲ) and Sb(Ⅴ) on their surfaces, and speculate the adsorption mechanism. The order of adsorption capacities (mg/g) of six soil minerals for Sb(Ⅲ)/Sb(Ⅴ) were as follows: ferrihydrite (101.4, 55.9)>ramsdellite (16.52, 7.58)>goethite (13.30, 5.67)>hematite (5.13, 3.70)>aluminum oxide (1.66, 1.69)>kaolinite (0.27, 0.51). Affected by the speciation of antimony and the surface potential of minerals, acidic conditions were favorable for the adsorption of Sb(Ⅴ), while the adsorption of Sb(Ⅲ) was less affected by pH. The Sb2O3 formed after deposition was characterizedin situ by Raman spectroscopy. Sb(Ⅴ) adsorbed on the mineral by adsorption at different concentrations, while Sb(Ⅲ) deposits on the mineral surface at higher concentrations. The BRIEF REPORT is available for this paper athttp://www.ykcs.ac.cn/en/article/doi/10.15898/j.ykcs.202404210093.